Glycerol-based SO3H-Carbon Catalyst: A green recyclable catalyst for the chemoselective synthesis of pentaerythritol diacetals - Ummadisetti, Chandrakala; Rachapudi, Badari Narayana Prasad; Bethala, Lakshmi Anu Prabhavathi Devi (European Journal of Chemistry, 2014)
Glycerol-based SO3H-functionalized carbon catalyst was demonstrated as an efficient and recyclable green catalyst for the chemoselective synthesis of pentaerythritol diacetals with aromatic aldehydes in the presence of ketones in excellent yields in toluene at 80 °C. In addition, the catalyst also has the capability for the deprotection of pentaerythritol diacetals in methanol at reflux temperature. The recovered catalyst without any pre-treatment was reused for 5 cycles without any deactivation and leaching into the reaction medium under optimum conditions.